EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN WINDOW SHOPPING PADA MATA PELAJARAN IPAS TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI KELAS IV SD MUHAMMADIYAH AMBARBINANGUN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the differences in IPAS learning achievement between students who apply the Window Shopping learning model and students who apply the Gallery Walk learning model in fourth-grade students of SD Muhammadiyah Ambarbinangun, and to determine the effectiveness of the Window Shopping learning model in teaching IPAS on the material of cultural diversity and local wisdom for fourth-grade students of SD Muhammadiyah Ambarbinangun. The type of research used in this study is experimental quantitative research with a Non-Equivalent Control Group design. The population of this study is 48, and the sample used consisted of 24 students from grade IV A as the control class using the Gallery Walk learning model and grade IV B as the experimental class using the Window Shopping learning model. The data collection methods used were observation and tests. The analysis techniques employed included prerequisite tests using normality tests and homogeneity tests, followed by hypothesis testing using t-tests or difference tests with an Independent Sample T-Test. The results of this study concluded that the Window Shopping learning model is effective in improving students' learning achievement in the IV-grade Social Science (IPAS) subject, particularly in the material on cultural diversity and local wisdom. This can be demonstrated by the differences between the experimental class and the control class. The study results showed the average learning outcomes for the experimental class were 60.62 in the pretest and 72.5 in the posttest. Meanwhile, the learning outcomes for the control class were 38.12 in the pretest and 51.04 in the posttest. The data processing technique used the t-test with Independent Sample T-Test. The Window Shopping learning model is more effective with a Sig. value of 0.000 < 0.05.